Topology control in wireless ad hoc and sensor networks - Santi, Paolo (Wiley, 2005)
"Topology Control in Wireless Ad Hoc and Sensor Networks makes the case for topology control and provides exhaustive coverage of TC techniques in wireless ad hoc and sensor networks, considering both stationary networks, to which most of the existing solutions are tailored, and mobile networks. The author introduces a new taxonomy of topology control and gives a full explication of the applications and challenges of this important topic." "This invaluable text will provide graduate students in Computer Science, Electrical and Computer Engineering, Applied Mathematics and Physics, and researchers in the field of ad hoc networking with a single reference resource on topology control. Professionals in wireless telecoms and networking system developers will also find it an indispensable guide."--BOOK JACKET.